Modern possibilities of diet therapy for functional disorders of the gastrointestinal tract in infants - O.H. Shadrin; V.P. Misnyk (Zaslavsky O.Yu., 2018)
The article presents the results of a detailed analysis of a questionnaire survey of 297 parents about the effectiveness of Nutrilon Comfort formula in infants with functional disorders of the gastrointestinal tract. The comprehensive positive effect of the formula on most symptoms is shown on day 7-14 of using this formula. A total elimination of symptoms of functional digestive disorders was noted in 75.8 % of children.